The Response to Dynamic Incentives in Insurance Contracts with a Deductible: Evidence from a Differences-in-Regression-Discontinuities Design - Tobias J. Klein; Martin Salm; Suraj Upadhyay (Institute of Labor Economics (IZA), 2020)
We develop a new approach to quantify how patients respond to dynamic incentives in health insurance contracts with a deductible. Our approach exploits two sources of variation in a differences-in-regression-discontinuities design: deductible contracts reset at the beginning of the year, and cost-sharing limits change over the years. Using rich claims-level data from a large Dutch health insurer we find that individuals are forward-looking. Changing dynamic incentives by increasing the deductible by â,¬100 leads to a reduction in healthcare spending of around 3% on the first days of the year and 6% at the annual level. The response to dynamic incentives is an important part of the overall effect of cost-sharing schemes on healthcare expendituresâ exteuro"much more so than what the previous literature has suggested.
Keywords: I13; H51; 330; health insurance; patient cost-sharing; dynamic incentives